Background for Cognitive Difficulties in Primary School Students - Kantorova E.V; Gorbachevskaya N.L (Moscow State University of Psychology and Education, 2020)
The article presents results of an empirical study on the key factors of difficulties in the formation of basic educational competencies in primary school children. The sample of the study involved 154 schoolchildren of a comprehensive school who were studied longitudinally for 5 years at different age stages: at preschool age, at the beginning of the first grade and at the end of the fourth grade. In fourth-grade schoolchildren, aged 10 to 11, we studied the ability to understand text while reading, the ability to solve mathematical problems, establish patterns in a number series, and also to perform tasks by analogy. The study used 12 methods of psychological and neuropsychological diagnostics which contained criteria for identifying procedural learning difficulties, characteristics of memorization and attention, hand-eye coordination of each student. A comparative analysis of the research results revealed the preconditions of difficulties in applying learning competencies in fourth-grade students. A set of psychological and neuropsychological indicators was identified, which enabled us to differentiate between the factors contributing to mathematical, linguistic and complex difficulties in the formation of learning competencies. These factors included problems in intellectual and cognitive sphere and procedural difficulties revealed in preschool and primary school children. The most significant precondition for all types of learning difficulties was the insufficient development of independent working skills at the beginning of schooling. The research results can be used to organize timely psychological and pedagogical assistance to students to prevent the occurrence of learning difficulties.